KONSEP PENDIDIKAN SEKS DALAM PERSPEKTIF ALQURAN - Hasiah, Hasiah (FORUM PAEDAGOGIK, 2016)
Sex in the view of Islam is an instinctive need that must be met. Only resoluting and stricting implementation regulated by religion so strictly can prohibite to do without any clear rules. Anticipation is not the deviation of sex as a way to implement sex education in the community, especially to children under age and adolescents.